Investigating the effect of pupil seating arrangements on student discussion in a mathematics classroom - Patel, Hetal (2012)
The main purpose of this action research study was to investigate the different types of verbal interactions by students in a mathematics classroom. The study used indicators to quantify different interactions using a voice recorder with one class of students in two different seating arrangements. The results shows students engaged in much more discussion when sat in groups compared with rows, however the proportion of mathematical discussion in rows was higher than in groups. The principal conclusion was the work required with students to ensure they could focus their discussion and how the teacher could facilitate this within lessons.